DECREASE OF BREAKAGE OF HIGH-STRENGTH WIRE AT METAL CORD TWIST ON MACHINES OF DOUBLE TORSION - B. A. Biryukov; Yu. V. Feoktistov; A. V. Vedeneyev (Литьë и металлургия)
Researches of the most often occurred surface defects of rolled wires, their modification at drawing and influence on technological process and quality of cold-drawn wire with regard to working conditions of hardware shops of BMZ are presented